2001
DOI: 10.1021/ja0100726
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Microscopy, Orbital-Mediated Tunneling Spectroscopy, and Ultraviolet Photoelectron Spectroscopy of Metal(II) Tetraphenylporphyrins Deposited from Vapor

Abstract: Thin films of vapor-deposited Ni(II) and Co(II) complexes of tetraphenylporphyrin (NiTPP and CoTPP) were studied supported on gold and embedded in Al-Al(2)O(3)-MTPP-Pb tunnel diodes, where M = Ni or Co. Thin films deposited onto polycrystalline gold were analyzed by ultraviolet photoelectron spectroscopy (UPS) using He I radiation. Scanning tunneling microscopy (STM) and orbital-mediated tunneling spectroscopy (STM-OMTS) were performed on submonolayer films of CoTPP and NiTPP supported on Au(111). Inelastic el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
305
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(357 citation statements)
references
References 40 publications
50
305
2
Order By: Relevance
“…The UPS spectrum corresponding to the bare Au substrate shows the same pattern and peak positions (2.7 and 4.3 eV vs EF) to that previously reported for clean Au surfaces and corresponds to the 5d bands. 38 At this point it is important to note that the escape depth (or attenuation length) λ of photoelectrons with 15 eV kinetic energy, i.e., below the Fermi edge photoemission for Au in a He(I) experiment, is approximately 8 Å for a compact hydrocarbon film. 39 Therefore, the sampling depth in the photoemission experiment at zero degrees take-off angle is approximately 24 Å (3 λ) hence this experiment samples the entire SAM layer and the SAM/Au interface.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…The UPS spectrum corresponding to the bare Au substrate shows the same pattern and peak positions (2.7 and 4.3 eV vs EF) to that previously reported for clean Au surfaces and corresponds to the 5d bands. 38 At this point it is important to note that the escape depth (or attenuation length) λ of photoelectrons with 15 eV kinetic energy, i.e., below the Fermi edge photoemission for Au in a He(I) experiment, is approximately 8 Å for a compact hydrocarbon film. 39 Therefore, the sampling depth in the photoemission experiment at zero degrees take-off angle is approximately 24 Å (3 λ) hence this experiment samples the entire SAM layer and the SAM/Au interface.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…[1][2][3] Many of these applications rely on the formation of thin films of ordered structures of porphyrins and related compounds. [4][5][6][7] Intermolecular interactions such as dipole-dipole, 8 hydrogen bonding, 8 and coordination 9 in porphyrin building blocks are being used to create selfassembled structures on surfaces with increasing sophistication. Itaya et al demonstrated that the ordering of porphyrin molecules on metal surfaces can be promoted by a passivating layer of iodine, which reduces the adsorbate-substrate interaction and facilitates surface diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…These processes will play a critical role in the so-called ''bottom-up'' strategy of nanofabrication. Therefore, understanding the organization of molecules on solid surfaces is important, both from a fundamental and applied perspective, for the construction of surface molecular nanostructures and nanodevices (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). A self-organized molecular pattern with control of structure and derived concomitant function could provide promising materials for the construction of nanodevices that cannot be prepared by conventional microfabrication.…”
mentioning
confidence: 99%